Quantitative multi-proxy climate reconstruction for MIS 3 in Central Europe based on precisely dated speleothems from Bleßberg Cave, Germany - Klose, Jennifer (Johannes Gutenberg-Universität Mainz, 2024)
Speleothems are sensitive paleoclimate archives and have been established as those during the past decades. They have the potential to continuously record valuable information about the past climate and can be precisely dated using U-series disequilibrium methods. The calculation of independent age-depth models and the analyses of various climate proxies, such as δ18O and δ13C, trace elements or fluid inclusions, allow to constrain high-resolution multi-proxy paleoclimate records. Dansgaard-Oeschger (DO) events are centennial- to millennial-scale climate oscillations during Marine Isotope Stage 3 (MIS 3, ca. 60 – 30 ka BP). While first discovered in Greenland ice cores evidence of these climate events has been observed on a global scale. DO events are characterised by a rapid warming followed by a gradual cooling, while MIS 3 in general is considered a rather cold period. Therefore, the fact that MIS 3 speleothem records from Central Europe are very limited has been attributed to too cold and dry conditions. Three flowstones from Bleßberg Cave, Germany which grew during MIS 3 were intensively studied during this thesis. A combined approach of solution-based (sampled by handheld drilling and micromilling) and in-situ Laser Ablation 230Th/U-dating has been used to create precise age models for samples with a complicated growth structure and growth phases smaller than 2 mm. The samples revealed several episodes of growth during MIS 3 primarily coinciding with DO events. The growth phases were established as its own proxy for favourable conditions for speleothem growth, i.e., periods with sufficient soil and vegetation cover above the cave and liquid water reaching the cave. In addition, a multi-proxy approach was used to gain more information about MIS 3 in Central Europe, which established the climate to deteriorate with ongoing progression of MIS 3. A particularly warm and prolonged growth phase coincided with DO14. Two short-term cold events were recorded within the event, highlighting the high sensitivity of ...